Data Note: Challenges when combining housing data from multiple sources to identify overcrowded households - Laura Scott; Yan Weigang; Marcella Ucci; Jessica Sheringham (International Journal of Population Data Science)
Background This project in one urban local authority in London (England) sought to assess the feasibility of generating locally-derived indices of overcrowding using data available to local councils on the population and their homes.